Therapeutic alliance: challenges and changes within a rapidly evolving context - Karademas, Evangelos C. (Psychology: the Journal of the Hellenic Psychological Society, 2021)
The aim of this short Commentary is to convey some thoughts and concerns that have arisen after reading the excellent articles included in this Special Issue. The focus will be on three particular points: (a) The differences that seem to exist, not so much regarding the general definition of therapeutic alliance, but rather with respect to the identification of the specific characteristics of this phenomemon and the factors that shape it. (b) The need to understand therapeutic alliance after taking into account the complex interactions that take place between several biological, psychological and social factors. Finally, (c) the impact of recent advancements, such as the great innovations in digital technology and health care, on therapeutic alliance. In any case, it is certain that our perception of therapeutic alliance will continue to evolve and change in the future.